Determinants of dropout from lifestyle interventions for overweight polycystic ovary syndrome: An exploratory analysis of randomized controlled trial - Min Xie; Siyu Zhou; Jing Wu; Xiaoyan Luo; Yichuan Guo; Lin Qiao; Jing Zhang (PLoS ONE, 2026)
Objective This exploratory analysis of a randomized controlled trial aimed to identify baseline predictors of dropout in overweight women with polycystic ovary syndrome (PCOS) participating in a lifestyle intervention program. Methods An exploratory analysis was conducted using data from a randomized controlled trial involving overweight or insulin-resistant women with PCOS aged 18–45. All participants received cyclic progestin, metformin, and a structured lifestyle intervention. Dropout was defined as proactive withdrawal, missing two consecutive visits, or loss of contact for more than six months. Univariate and adjusted multivariable logistic regression models were used to identify factors associated with dropout. Results Among the participants, 61.06% (n = 69) dropped out within one year. No significant differences were observed in baseline demographic, clinical, biochemical, psychological, or dietary characteristics between completers and dropouts. However, baseline physical activity level (PAL), objectively measured using an accelerometer, was identified as the strongest predictor of dropout. Each 0.3-unit increase in PAL was associated with a 29.6% reduction in the likelihood of dropout. Conclusion Baseline PAL is strongly associated with the risk of dropout. Screening for PAL in women with PCOS is recommended, and those with lower PAL should receive personalized support in addition to lifestyle interventions to improve adherence and promote weight loss.